(3fXe GdeYdheGJ GdGOGQjIs - (3SjO UGHQ(B, (3JYdHs ((3YeGf(B:s (3OGQ GdacQ(B,s, 2011)
(3JYQjaGJ egeI Mhd GdHjGfGJ h GdeYdheGJ , GdMGSH GdBdj h GdeYGdLI GdGdcJQhfjI , bhGYO GdHjGfGJ , fePLI GdHjGfGJ h YdGbGJ GdcjGfGJ , eGgjI fXe GdeYdheGJ h eQGMd GdeYGdLI , OQGSI fXGe GdeYdheGJ ef MjK ObI GdeNQLGJ , GdYdGbI HGdHjFI , QSejI JhGLO GdfXGe , JcGed GdfXe GdaQYjI , GdYdGbI eY GdfXe GdCNQi h JTZjd GdfXGe , CfhGY fXe GdeYdheGJ ef MjK GdJNUUGJ GdehVhYjI , GdCaQGO GdPj dge OhQ aj fLGM fXe GdeYdheGJ , JMdjd h JUeje fXe GdeYdheGJ GdGOGQjI h HfGA gPg GdfXe , GdGfJQfjJ h fXe GdeYdheGJ GdGOGQjI , JCejf fXe GdeYdheGJ GdGOGQjI h CNjQG CeKdI dHYV fXe GdeYdheGJs
(3eUWdMGJ U(B.323 (3; eQGLY U(B.331s
Keywords: (3fXe GdeYdheGJ GdGOGQjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s